The Meta and Para OH Substitution Effect on C-Phenyl-Nitrilimine Bond-Shift Isomers - Ferreira, Gil A.; Nunes, Claudio M.; Jesus, A. J. Lopes; FAUSTO, RUI (Wiley-VCH Verlag GmbH, 2023)
The geometric and electronic structure of 1,3-dipolar species, in particular of nitrile imines, can be surprisingly intricate. A particular example is the C-phenyl-nitrilimine, which exists as two energy minima that constitute bond-shift isomers. To examine the effect of substituents in the phenyl ring, here we investigate the meta and para OH substituted derivatives. These two nitrile imines were generated in an argon matrix by UV-irradiation of 2H-tetrazole precursors and found to photoisomerize to carbodiimides via 1H-diazirines. The different effects of the OH substitution in meta and para positions on the bond-shift isomerism are rationalized with the support of Natural Resonance Theory and Hirshfeld atomic charges. The understanding of how substitution affects the structural characteristics of C-phenyl-nitrilimines, opens a door to modulate the chemistry of those compounds (e. g. in cycloaddition reactions) by appropriate tuning of their substitution (substituent type and position).
Keywords: Nitrile Imines; Geometric and Electronic Structure; Matrix-isolation; Ir Spectroscopy; Computational Chemistry